An analysis of pharmacists' workplace patient safety perceptions across practice setting and role characteristics - Reginald Dilliard; Nicholas E. Hagemeier; Brady Ratliff; Rebecca Maloney (Elsevier, 2021)
Background: Lay press investigations have been published that describe pharmacist errors and the workplace environment in the community pharmacy setting. However, recent studies that explore pharmacists' perceptions of patient safety in the workplace are limited. Objectives: 1) To describe pharmacists' perceptions of workplace patient safety; 2) To compare pharmacists' perceptions of workplace patient safety across practice setting type, pharmacist roles, average hours worked per shift, and average hours worked per week. Methods: Actively licensed Tennessee pharmacists were recruited from January 1 and June 30, 2019 to complete a 13-item survey of workplace patient safety perceptions (N=1391). Descriptive statistics were calculated, and nonparametric statistical tests employed to compare differences in perceptions across practice setting type, pharmacist roles, and hours worked per shift and per week. Results: Statistically significant differences in workplace patient safety perceptions were noted across practice setting type (p values <.001) and pharmacist roles (p values <.001). The extent to which pharmacists agreed/strongly agreed that their employer provides a work environment that allows for safe patient care ranged from 29.7% of chain community pharmacists to 85% of compounding pharmacists. Fifty-two percent of staff pharmacists, 56.5% of relief pharmacists, and 58.5% of managers/pharmacists in charge agreed or strongly agreed that their employer provides a work environment that allows for safe patient care, whereas 89.3% of regional managers/directors/vice-presidents and 72.5% of clinical/specialty pharmacists indicated the same. Average hours per shift was inversely correlated with perceptions of workplace patient safety (p values <.001). Conclusion: Tennessee pharmacists' perceptions of workplace patient safety varied widely across practice setting type and pharmacist roles. Perceptions of safety were notably lower in the chain community pharmacy setting. Additional research is warranted to better understand the relationship between pharmacist perceptions and quantifiable patient safety metrics, particularly in the chain community pharmacy setting.